Case report: Germline CHEK2 mutation is associated with a giant cell glioblastoma - Bi, Yongfeng; Wan, Dong; Chen, Si; Chen, Huafei; Guo, Lingchuan; He, Xiaoshun; Rong, Rong; Xiao, Jinyuan; Gao, Wei; Xiao, Sheng (Frontiers in Oncology, 2024)
Giant cell glioblastoma often exhibits genome instability and is frequently associated with mutations in genes involved in DNA repair pathways including TP53 and DNA mismatch repair genes. Several germline mutations have been identified in giant cell glioblastoma, including mutations of MSH1 and MSH2, TP53, and POLE. We have documented a case of a germline mutation in CHEK2, another gene crucial to DNA repair, in a patient with giant cell glioblastoma. The CHEK2 mutation was inherited from the patient’s father, who had a history of gastric cancer and renal cell carcinoma. In addition to the germline CHEK2 mutation, the giant cell glioblastoma exhibited a genome-wide loss of heterozygosity, a characteristic observed in a subset of giant cell glioblastomas. Additional mutations detected in the tumor included TP53, PTEN, and a PTPRZ1-MET fusion. This represents the first reported case of a CHEK2 germline mutation in giant cell glioblastoma, further supporting the significance of impaired DNA repair mechanisms in the development of this disease.